The effect of UVB radiation on the optical quality of rainbow trout eye-lenses - Marta Kocemba; Edward Waller; Anthony J. Waker (Scientific Reports)
Abstract This study followed changes in the optical quality of teleost eye-lenses following exposure to non-ionizing UVB radiation and was carried out as an adjunct to a wider ongoing study on the effects of ionizing radiation on vertebrate eye-lenses. The lenses of rainbow trout (Oncorhynchus mykiss) were excised and cultured in vitro, then exposed to 0.2 J cm−2 of UVB radiation. The optical quality of the lenses was measured daily until the end-point of full surface clouding was observed. Optical quality assessment was accomplished through laser focal analysis, which is a method of measuring changes in lens optical function while the lens is still transparent. Lens optical quality is quantified by measuring focal lengths and focal length variability in each lens. Our study found a significant difference in lens quality in irradiated lenses compared to control lenses 11 days after irradiation. Irradiated lenses also showed a reduction in optical quality on the last day of transparency before lens damage progressed to full surface clouding. Irradiated lenses also maintained transparency in culture for longer than control lenses. Therefore, we have shown that UVB decreases the optical quality of vertebrate eye-lenses and potentially induces a stress response in the maintenance of lens transparency.